Comparative analysis of the scope of European Union paediatric investigation plans with corresponding orphan designations. Issue 5 (31st October 2017) - Ecker, Andrea; Mariz, Segundo; Naumann-Winter, Frauke; Norga, Koenraad; Barisic, Ingeborg; Girard, Thomas; Tomasi, Paolo; Mentzer, Dirk; Sepodes, Bruno
Abstract : Background: Market forces may not be sufficient to stimulate research and development of medicines for small patient populations, such as children and patients with rare diseases. Both the European Union Orphan and Paediatric Regulations were introduced to address the unmet public health needs of these smaller patient populations through the use of incentives, rewards and obligations. Developers for new medicines for rare diseases must agree a paediatric investigation plan (PIP) or waiver with the European Medicines Agency's (EMA) Paediatric Committee (PDCO), and can also apply for an orphan designation (OD) from the EMA's Committee of Orphan Medicinal Products (COMP). The scope of both the OD and the PIP (or waiver) is defined by the agreed condition. Objectives: The aim of this study was to analyse the approach of PDCO and COMP in defining the appropriate condition for a PIP or OD, respectively, in order to investigate potential challenges in the paediatric development of orphan medicines which have to meet the requirements of both legislations. Methods: A comparative analysis of PIP conditions and OD conditions was performed for medicines that have been reviewed by both Committees. Results: We found that in the substantial majority of cases there is no divergence between the conclusions of COMP and PDCO with regard to the condition for which a medicine is to be developed. Conclusion: These findings demonstrate that a collaborative approach allows both Regulations to work synergistically to foster pharmaceutical development for rare diseases in childhood.